Aramid-Zirconia Nanocomposite Coating With Excellent Corrosion Protection of Stainless Steel in Saline Media - Nazeer, Ahmed Abdel; Al Sagheer, Fakhreia; Bumajdad, Ali (Frontiers in Chemistry, 2020)
Resistance to stainless steels corrosion in marine based industries requires more surface improvement and enhanced protection by utilizing surface coatings. Herein, a thermally stable aramid–zirconia nanocomposite has been successfully prepared by the sol–gel method to produce zirconia network-structure bonded to the polymer chain. Using thermal gravimetric analysis (TGA), the residue mass of zirconia retained after the thermal degradation of aramid-zirconia film was determined and found to be 10% by mass. The investigated nanocomposite (using 10% zirconia) was coated on the stainless-steel surface through a facile and effective spin coating method and examined its protection in saline solution (3.5 % NaCl). The aramid–zirconia nanocomposite coating (Ar-Zr10) was found to provide an outstanding corrosion resistance to steel surface which led to protect it against the corrosive marine environment. The electrochemical impedance (EIS) measurements were carried out to evaluate steel resistance against dissolution in chloride solution in the absence and presence of the investigated coatings showed corrosion protection efficiency of 99.3% using Ar-Zr10 compared to 92.1% using pure aramid. Moreover, the potentiodynamic polarization (PDP) plots showed pronounced decrease in the corrosion current values which confirmed the formation of passive layer which mitigate the corrosion reaction and ions diffusion. The water contact angle of stainless-steel coated with pure aramid and the aramid–zirconia was found to be 84.2° and 125°, respectively confirming the hydrophobic nature of the hybrid coating Ar-Zr10. On the other hand, the results achieved through the electrochemical and surface techniques were used to clarify the